Salmonella Typhimurium's Transthyretin-Like Protein Is a Host-Specific Factor Important in Fecal Survival in Chickens - Hennebry, Sarah C.; Sait, Leanne C.; Mantena, Raju; Humphrey, Thomas J.; Yang, Ji; Scott, Timothy; Kupz, Andreas; Richardson, Samantha J.; Strugnell, Richard A. (PloS one, 2012)
The transthyretin-like protein (TLP) from Salmonella enterica subspecies I is a periplasmic protein with high level structural similarity to a protein found in mammals and fish. In humans, the protein homologue, transthyretin, binds and carries retinol and thyroxine, and a series of other, unrelated aromatic compounds. Here we show that the amino acid sequence of the TLP from different species, subspecies and serovars of the Salmonella genus is highly conserved and demonstrate that the TLP gene is constitutively expressed in S. Typhimurium and that copper and other divalent metal ions severely inhibit enzyme activity of the TLP, a cyclic amidohydrolase that hydrolyses 5-hydroxyisourate (5-HIU). In order to determine the in vivo role of the S. Typhimurium TLP, we constructed a strain of mouse-virulent S. Typhimurium SL1344 bearing a mutation in the TLP gene (SL1344 ΔyedX). We assessed the virulence of this strain via oral inoculation of mice and chickens. Whilst SL1344 ΔyedX induced a systemic infection in both organisms, the bacterial load detected in the faeces of infected chickens was significantly reduced when compared to the load of S. Typhimurium SL1344. These data demonstrate that the TLP gene is required for survival of S. Typhimurium in a high uric acid environment such as chicken faeces, and that metabolic traits of Salmonellae in natural and contrived hosts may be fundamentally different. Our data also highlight the importance of using appropriate animal models for the study of bacterial pathogenesis especially where host-specific virulence factors or traits are the subject of the study.